ANALISIS KESULITAN SISWA KELAS V DALAM MENULIS TEKS NARASI TEMA 7 SUBTEMA 2 DI SDN MOJOAGUNG 01 - Rohmawati, Nur; Mushafanah, Qoriati; Mudzanatun, Mudzanatun (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2022)
The goal to be achieved by the researcher is to describe the difficulties of students in writing narrative texts for class V theme 7 sub-theme 2 for the 2020/2021 academic year at SDN Mojoagung 01. The research method used is descriptive qualitative research. The research subjects were students of class V SDN Mojoagung 01. Based on the results of research on student questionnaires, as many as 8 students had difficulty writing the contents of ideas that were in accordance with the topic, as many as 9 students had difficulties in the suitability of content with titles, as many as 15 students had difficulties in diction/word choice, as many as 17 students had difficulties in using spelling, and 14 students had difficulties with the neatness of writing. Based on the results, it was found that the level of students' ability to write narrative texts was 6 students who were not good enough, 16 students were good enough, and 2 students were good. Difficulties experienced by students in aspects of diction/word choice, spelling use, and writing neatness. Implementation for the world of education is to improve education in the future that is needed to know the difficulties of students in writing narrative texts.